Faktor-Faktor yang Berhubungan Dengan Kunjungan Ibu Dengan Balita ke Posyandu - Alfrida Fitriyah; Niken Purbowati; Willa Follona (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2019)
Posyandu is useful to empower communities and to provide the easiest of obtaining basic health services. The objectives of this study was conducted to determine the related factors with the toodlers visits to Posyandu in the Working Area of Health Center Pegangsaan Dua B, Kelapa Gading, North Jakarta in 2018. This study was an analitic descriptive with cross sectional design. There were 75 samples of toddlers mothers randomly chosen in 6 Posyandu. The results obtained are well behaved toddler mother as much as 68%. There are four variables that were statistically related with the behavior visits to Posyandu namely: there were more on good knowledge, short distance, and positive thinking to cadres and health workers. Multivariate analysis with prediction logistic regression method produces dominant variable that is distance, and become confounding is role of cadre. It is further recommended to perform and improve the monitoring of health promotion efforts with direct supervision to Posyandu and provide conseling to the public about the existing activities in Posyandu.